Effect of sex and protein level on the intermediary metabolism, growth, deposition of nutrients and profile of volatile compounds of silver catfish (Rhamdia quelen). (30th August 2017) - Adorian, T.J.; Mombach, P.I.; Goulart, F.R.; Pianesso, D.; Fagundes, M.B.; Wagner, R.; Lazzari, R.; Radünz Neto, J.; da Silva, L.P.
Abstract: This study aimed at evaluating the intermediary metabolism, growth, nutritional deposition and volatile compounds of fillet of female and male silver catfish created in cages having commercial diets at two levels of crude protein. A total of 1, 200 silver catfish were randomly distributed in 12 cages with initial weight of 130.05 ± 0.14 g and visually sexed. Commercial diets with 280 g/kg and 320 g/kg of crude protein were offered twice a day in the amount of 30 g/kg their biomass/day, for 90 days. At the end of the experimental period, biometry was performed to collect data, blood and tissue for later determination of plasma metabolites, hepatic metabolites, digestive enzymes, volatile compounds, deposition of nutrients and calculation of growth variables. There were metabolic differences due to the sex of silver catfish, reflecting greater productive efficiency on the females. For the plasma metabolites, in male, there were higher values of triglycerides and free amino acids than in female. For hepatic glucose, males fed with diet containing 280 g/kg of crude protein showed higher values. For protein and free amino acids, the interaction between males that received 320 g/kg of crude protein was higher. In males, there were higher values of AST and hepatic glycogen than in females. In turn, hepatic ammonia was higher in females. There was greater activity of acid protease enzymes and trypsin in the silver catfish that received diets containing 320 g/kg of crude protein. Regardless of sex, in this cultivation phase, diets with 320 g/kg of crude protein provided better performance to silver catfish. The profile of volatile compounds suggests mild odour for the fillet of silver catfish, which can be a competitive advantage of the species.